2005
DOI: 10.1108/01437720510587262
|View full text |Cite
|
Sign up to set email alerts
|

Fitting in organizational values

Abstract: PurposeThe current leadership literature has paid little attention to understanding the intervening mechanism by which leaders influence followers. In order to partially bridge this gap, the article aims to present a value‐fit charismatic leadership theory which focusses on the key intervening mechanism – person‐organization values fit.Design/methodology/approachThe model was tested empirically on 180 participants, including 51 managers and 129 employees from 37 large‐scale companies in Taiwan.FindingsBased on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Two studies suggested that supervisors and the support they provide are related to employees' fit perceptions. Huang, Cheng, and Chou (2005) found that charismatic leadership had a positive relationship with employees' perceptions of PO fit, and Chen and Chiu (2008) reported that supervisory support was correlated highly (r = .57) with perceived PO fit. Although these studies are prone to common source bias, they provide preliminary evidence that supervisors can influence employees' fit perceptions.…”
Section: Future Directionsmentioning
confidence: 99%
“…Two studies suggested that supervisors and the support they provide are related to employees' fit perceptions. Huang, Cheng, and Chou (2005) found that charismatic leadership had a positive relationship with employees' perceptions of PO fit, and Chen and Chiu (2008) reported that supervisory support was correlated highly (r = .57) with perceived PO fit. Although these studies are prone to common source bias, they provide preliminary evidence that supervisors can influence employees' fit perceptions.…”
Section: Future Directionsmentioning
confidence: 99%
“…The findings from these authors indicated that the leadership styles of head teachers have some influence on academic performance of students. Based on this background, the following hypothesis are developed: H1a: Instructional leadership has significant positive impact on school performance H1b: transactional leadership has significant positive impact on school performance H1c: transformational leadership has significant positive impact on school performance Studies such as Krishnan, (2005) and Huang & Chou, (2005) have demonstrated the significant relationship between leadership styles and employees' satisfaction in business organization. In this sense it is established that, the kind of leadership style exhibited in an organization determines the level of employee job satisfaction and their commitment towards the duty.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Empirical studies conducted since 1999 have proved that congruence of personal and organizational values is positively related to employees' satisfaction with work (Lauver & Kristof-Brown, 2001;Silverthorne, 2004;Verplanken, 2004;Westerman & Cyr, 2004;Siegall & McDonald, 2004;Huang et al, 2005;Ostroff et al, 2005;Lawrence, 2006;Cennamo & Gardner, 2008;Edwards & Cable, 2009;Greguras & Diefendorff, 2009;Chiang & Birtch, 2010;Kallas et al, 2010;Posner, 2010;Suar & Khuntia, 2010;Leung & Chaturvedi, 2011;Ahmad & Veerapandian, 2012;etc. ), commitment to the organisation (Finegan, 2000;Silverthorne, 2004;Westerman & Cyr, 2004;Huang et al, 2005;Ostroff et al, 2005;Lawrence, 2006;Cennamo & Gardner, 2008;Greguras & Diefendorff, 2009;Chiang & Birtch, 2010;Posner, 2010;Suar & Khuntia, 2010;Leung & Chaturvedi, 2011;Agarwal & Sagar, 2012;etc. ), identification with the organisation (Cable & DeRue, 2002;Edwards & Cable, 2009;etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…), proactiveness (Suar & Khuntia, 2010), delegation of decision-making (Ren, 2010), contextual activity, when the employee performs more than stated in his / her job description (Lauver & Kristof-Brown, 2001;Vogel & Feldman, 2009;etc. ), and influences employees' performance results (Huang et al, 2005;Lawrence, 2006;Greguras & Diefendorff, 2009;Suar & Khuntia, 2010;etc.). It should be noted that value congruence reduces employee turnover (Lauver & Kristof-Brown, 2001;Cable & DeRue, 2002;Siegall & McDonald, 2004;Westerman & Cyr, 2004;Ostroff et al, 2005;Cennamo & Gard-ner, 2008;Edwards & Cable, 2009;etc.…”
Section: Literature Reviewmentioning
confidence: 99%